(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2015)
How can a work of art reach beyond the borders of the medium to which it would logically seem to belong? Following a brief reflection upon an important essay by Rosalind Krauss, ‘Reinventing the Medium’, this contribution focuses specifically on one of Jeff Wall’s works, allowing the author to deal more directly with the issue of the dialogue between different mediums. Through the analysis of Dead Troops Talk, the aim of the article is to demonstrate: first, how the socalled photograph does not exploit the potential of its own medium, but instead applies a compositional strategy borrowed from the pictorial medium; and second, how the same photograph undermines the genre of historical painting (to which it is linked via its compositional strategy) by putting the fictitious — and cinematographic — figure of the zombie at the center of the representation.